Flora in Beja Lexicon - Blažek, Václav (Folia Orientalia, 2021)
In the present contribution the Beja botanical terminology is analyzed from the point of view of semantic motivation. The study is limited only to the unborrowed part of the botanical lexicon (with some exceptions), together 76 terms. First 51 terms are etymologized with help of external comparisons with probable cognates in other Cushitic or Afroasiatic languages. The last 25 terms are understandable from the point of view of internal etymology and their semantic motivation is more transparent than in the preceding cases.